2020
DOI: 10.1017/gov.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Bread or Circuses? Repoliticization in the Italian Populist Government Experience

Abstract: The majority view within political science is that populism is best understood as a (thin) ideology. We problematize the ideational approach by broadening the scope of analysis, linking populism to the rise of long-term generalized anti-political sentiments, against interpretations that tend to tie the populist wave to conjunctural factors related to recent crises. We argue that the essence of populism lies at the intersection of the ‘material constitution’ of advanced industrial democracies (that is, how macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The change of Italian government in 2018 to include the Lega, and specifically the appointment of party leader Matteo Salvini as minister of interior, was hugely consequential for national asylum policy. Resistance to further settlement of asylum seekers was central to his approach, as shown by the infamous closure of ports in June 2018 and the restrictions imposed by the so-called ‘Salvini Decree’ in September 2018 (Baldini and Giglioli 2020: 14–15). His appointment also proved to be a decisive turning point in the emergence of multilevel governance arrangements, and resulting changes in local asylum policy in Cascina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of Italian government in 2018 to include the Lega, and specifically the appointment of party leader Matteo Salvini as minister of interior, was hugely consequential for national asylum policy. Resistance to further settlement of asylum seekers was central to his approach, as shown by the infamous closure of ports in June 2018 and the restrictions imposed by the so-called ‘Salvini Decree’ in September 2018 (Baldini and Giglioli 2020: 14–15). His appointment also proved to be a decisive turning point in the emergence of multilevel governance arrangements, and resulting changes in local asylum policy in Cascina.…”
Section: Resultsmentioning
confidence: 99%
“…Although both coalitions collapsed prematurely in 2019, these cases offer empirical material for the study of the consequences of populism in power. Regarding the policy consequences, research has already shown that the FPÖ and the Lega introduced a number of exclusionary measures consistent with their ideological aims (Baldini and Giglioli 2020: 14–16; Rathgeb 2020).…”
mentioning
confidence: 99%
“…Moreover, the provocative and polarizing content is very effective in setting the agenda and influencing the public debate, as shown by a plethora of legacy media discussions over the conflict between Salvini and Rackete, and by Rackete's decision to press charges against Salvini for defamation (Rackete publicly motivated this decision by claiming that Salvini used social media to spread hate speech, threats, and insults 6 ). In general, the mediatized attacks to sea-rescue NGOs pursued by Salvini on social media have been quite successful in increasing the support for anti-migration policies (Baldini and Giglioli, 2020) and media attention toward the politicization of migration (Bailo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The dismal performance of the PD (the worst in the party’s history) exposed the deep crisis of legitimation of the ‘neoliberal-progressive Europeanism’ associated in Italy with centre-left political forces (Cozzolino, 2021: 140–141). At the same time, the success of the M5S and the League vindicated their strategies aimed at re-politicising certain key socio-economic issues, opposing national and supranational technocracies, and denouncing the de-democratisation of European integration (see Baldini and Giglioli, 2021; Caiani, 2019). Moreover, the rise of the League clearly showed its ability to capitalise upon the ‘migration crisis’ (often linking immigration with the issues of unemployment and low wages) (Caiani and Padoan, 2021) and to keep it at the centre of the political agenda, despite a continuous decline in the number of migrant arrivals (Strazzari and Grandi, 2019).…”
Section: The Rise Of the M5s And The League: Neoliberalisation In A N...mentioning
confidence: 99%